2023
DOI: 10.3390/ijms24031953
|View full text |Cite
|
Sign up to set email alerts
|

Sly-miR398 Participates in Cadmium Stress Acclimation by Regulating Antioxidant System and Cadmium Transport in Tomato (Solanum lycopersicum)

Abstract: Cadmium (Cd) pollution is one of the major threats in agricultural production, and can cause oxidative damage and growth limitation in plants. MicroRNA398 (miR398) is involved in plant resistance to different stresses, and the post-transcriptional regulation of miR398 on CSDs plays a key role. Here, we report that miR398 was down-regulated in tomato in response to Cd stress. Simultaneously, CSD1 and SOD were up-regulated, with CSD2 unchanged, suggesting CSD1 is involved in miR398-induced regulation under Cd st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…These alterations were further validated using qRT-PCR and SOD enzyme activity analyses. Similar studies showed that miR398 participated in controlling abiotic stress by targeting CSD1/CSD2 in rice [70], grapevine [71], and tomatoes [72]. Therefore, we speculate that MeJA treatment could increase the expression of CSD2 and further enhance the activity of SOD through miR398 in A. venetum, thereby enhancing the tolerance of A. venetum plants to various environmental stresses.…”
Section: Discussionsupporting
confidence: 62%
“…These alterations were further validated using qRT-PCR and SOD enzyme activity analyses. Similar studies showed that miR398 participated in controlling abiotic stress by targeting CSD1/CSD2 in rice [70], grapevine [71], and tomatoes [72]. Therefore, we speculate that MeJA treatment could increase the expression of CSD2 and further enhance the activity of SOD through miR398 in A. venetum, thereby enhancing the tolerance of A. venetum plants to various environmental stresses.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, Yan et al found that growth inhibition, oxidative damage, and antioxidant enzyme disorders are more pronounced in tomato plants overexpressing miR398 under cadmium stress than in WT plants. Conversely, miR398 down-regulation exerts a protective effect against cadmium stress in tomato plants by regulating antioxidant enzyme activities alongside cadmium uptake and translocation [51].…”
Section: Mirnas and Heavy Metal Stressmentioning
confidence: 99%
“…Over the past two decades, researchers have identified a large number of plant miRNAs in major crops and model plants that act in response to abiotic stresses. Considering the continuous improvement in high-throughput and deep sequencing technologies, we can use these sequencing tools to perform genome-wide miRNA expression analysis under abiotic stresses and efficiently and rapidly identify multiple miRNA targets, including degradome sequencing, which enables the identification of the mechanisms of action of a large number of miRNAs [105]. Currently, most studies are focused on the identification of downstream target genes of miRNAs.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%